AlgR, a response regulator controlling mucoidy in Pseudomonas aeruginosa, binds to the FUS sites of the algD promoter located unusually far upstream from the mRNA start site. - Mohr, C D (1991)
Strong transcriptional activation of algD, a key event in the overproduction of alginate and establishment of mucoidy in Pseudomonas aeruginosa, depends on the functional algR gene. The predicted gene product of algR shows homologies to response regulators from bacterial signal transduction systems. The algR gene was overexpressed in Escherichia coli, its product (AlgR) was purified by utilizing its apparent affinity for heparin, and its sequence was verified by partial amino acid sequence analysis. AlgR was found to interact directly with the algD promoter. Deletion mapping analysis, in conjunction with mobility shift DNA-binding assays, indicated the presence of three regions within the algD promoter capable of specifically binding AlgR. A relatively weak interaction was observed with the algD promoter fragment containing the region immediately upstream of the algD mRNA start site (-144 to +11). However, when fragments spanning regions located very far upstream from the algD mRNA initiation site (-533 and -332) were used, strong specific binding was observed. These regions were separated by a DNA segment not binding AlgR and spanning positions -332 to -144. DNase I footprinting analysis further established the presence of discrete AlgR binding sites overlapping with FUS, the far-upstream sites required for full induction of algD transcription and its environmental modulation. There were two distinct binding sites: RB1, spanning nucleotides -479 to -457, and RB2, spanning nucleotides -400 to -380. Both of these sequences shared a highly conserved core region, ACCGTTCGTC. These results established a direct interaction of AlgR with the algD promoter and revealed an arrangement of binding sites highly unusual for response regulators of the AlgR type.